Competitiveness of Enterprises Established In Rural Areas: Insights from Hilly Terrain of India - Kishor, Nawal; Lal, Chaman (British Journal of Marketing Studies, 2016)
Competitiveness of various types of enterprises is utmost important if an entrepreneurial society has to secure economic survival in the liberalized and globalized era. Firm’s competitiveness assures the long-term economic and social growth of any country. The present study aims; first to analyze the competitiveness of the enterprises established in hilly region; second to determine the sector-wise level of competitiveness of the enterprises established in the rural areas of India; and third to provide the suggestions to improve the competitiveness of these enterprises to secure the long term growth in competitive era. In this study, the researchers make use of primary data which is collected through schedule method using purposive sampling. Item & reliability analysis, and factor analysis are applied to analyze the level of competitiveness of the enterprises along with ANOVA, and descriptive & t-statistics. The findings reflect that level of competitiveness of enterprises established in the rural areas of hilly terrain significantly low and differ from each other and that too from industrial area wise. Locations of the enterprises have significant contribution in the competitiveness of the enterprises. The study may provide new insights to policymakers and stakeholders to improve the competitiveness of the enterprises